Monolithically integrated wavelength‐multiplexed DFB laser array with laterally coupled quarter‐wave phase‐shift gratings defined by interference lithography. Issue 18 (1st August 2014) - Li, Jingsi; Cheng, Julian
Abstract : The first monolithically integrated laterally coupled, multi‐wavelength distributed feedback (DFB) laser array using first‐order sidewall sampled gratings with equivalent quarter‐wave phase shifts defined by interference lithography is experimentally demonstrated. The elements of the monolithic DFB laser array lase strongly monomode, with an average side mode suppression ratio of ∼37.3 dB and with a uniform wavelength spacing of ∼7.3 nm. The output power under 100 mA bias current ranges from 11.4 to 14.1 mW. The proposed method offers a practical and low‐cost method for the fabrication of multi‐wavelength monolithic DFB laser arrays without regrowth or e‐beam lithography.